Infrastructure Gap in South Asia : Inequality of Access to Infrastructure Services - Biller, Dan; Andres, Luis; Herrera Dappe, Matias (World Bank Group, Washington, DC, 2014)
The South Asia region is home to the largest pool of individuals living under the poverty line, coupled with a fast-growing population. The importance of access to basic infrastructure services on welfare and the quality of life is clear. Yet the South Asia region's rates of access to infrastructure (sanitation, electricity, telecom, and transport) are closer to those of Sub-Saharan Africa, the one exception being water, where the South Asia region is comparable to East Asia and the pacific and Latin America and the Caribbean. The challenge of increasing access to these services across the South Asia region is compounded by the unequal distribution of existing access for households. This study improves understanding of this inequality by evaluating access across the region's physical (location), poverty, and income considerations. The paper also analyzes inequality of access across time, that is, across generations. It finds that while the regressivity of infrastructure services is clearly present in South Asia, the story that emerges is heterogeneous and complex. There is no simple explanation for these inequalities, although certainly geography matters, some household characteristics matter (like living in a rural area with a head of household who lacks education), and policy intent matters. If a poorer country or a poorer state can have better access to a given infrastructure service than in a richer country or a richer state, then there is hope that policy makers can adopt measures that will improve access in a manner in which prosperity is more widely shared.